The distinctive features of 70ies in S. Baturyn’s novel «Shyzgara» : the role of specialties and art details in a text - Даниленко, Людмила Вікторівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article traces the art specialties of the novel «Shizgara» of the modern Ukrainian writer S. Baturyn. The author of the article pays the attention to art details and particularities of the composition. The author characterized the containable meaning of details used in writer’s remarks. These details illustrate the everyday life of the young inhabitants of the Pechersk district and complete the multi-dimensional background of the text. Basing on this background, we can trace characters’ destinies and vicissitudes of time. It was stressed that the writer has his own style of using details. In order to create the special intimate mood, he uses his own memories, and for keeping reliability he refers to Wikipedia. The writer pays the attention to art details when describing the characters’ appearances. We can trace the writer’s hand in characters’ portraits. Using of colors and scents as art details is also characterized. The author of the article proves that the art detail is in harmony with the leitmotiv of the novel. It illustrates positive nostalgic mood, light irony, well-aimed humor, describes specifies of 70ies.